2016
DOI: 10.1111/pace.12962
|View full text |Cite
|
Sign up to set email alerts
|

The QT Interval as a Noninvasive Marker of Atrial Refractoriness

Abstract: Introduction Atrial refractoriness may be an important determinant of atrial fibrillation (AF) risk, but its measurement is not clinically accessible. Because the QT interval predicts incident AF and the atrium and ventricle share repolarizing ion currents, we investigated the association between an individual’s QT interval and atrial effective refractory period (AERP). Methods In paroxysmal AF patients presenting for catheter ablation, the QT interval was measured from the surface 12-lead ECG. The AERP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A prolonged QT‐interval has been shown to predict the development of AF, and longer QTc intervals increase the heart's vulnerability to ventricular dysrhythmias [31]. Prolonged QTc intervals also reflect the atrial effective refractory period (AERP) [32], and a prolonged AERP is associated with an increased risk of AF [33]. A high sodium intake may affect QT‐interval length.…”
Section: Discussionmentioning
confidence: 99%
“…A prolonged QT‐interval has been shown to predict the development of AF, and longer QTc intervals increase the heart's vulnerability to ventricular dysrhythmias [31]. Prolonged QTc intervals also reflect the atrial effective refractory period (AERP) [32], and a prolonged AERP is associated with an increased risk of AF [33]. A high sodium intake may affect QT‐interval length.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, prolonged QTc interval caused atrioventricular dyssynchrony that might aggravate LA remodeling . Atrial effective refractory period (AERP) was suggested as an important determinant of reentry which is a likely fundamental mechanism leading to AF and Nguyen et al . found a positive association between QTc interval and the AERP.…”
Section: Discussionmentioning
confidence: 99%
“…The ARIC study examined prolonged QT interval corrected by using the Framingham formula (QTc) as a predictor of incident AF, and showed that prolonged QTc predicts a roughly 2-fold increased risk of AF [25]. QTc interval reflects the atrial effective refractory period (AERP), suggesting that QTc interval may be used as a marker of atrial refractoriness relevant to assessing AF risk and mechanism-specific therapeutic strategies [26]. Hypercapnia has also been implicated in AF occurrence in COPD.…”
Section: Pathophysiological Mechanisms Implicating Chronic Obstructive Pulmonary Disease In Atrial Fibrillationmentioning
confidence: 99%